Association Between Non-Iron-Deficient Anemia and Insomnia Symptoms in Community-Dwelling Older Adults: The Baltimore Longitudinal Study of Aging. (20th January 2017) - Chen-Edinboro, Lenis P; Murray-Kolb, Laura E; Simonsick, Eleanor M; Ferrucci, Luigi; Allen, Richard; Payne, Martha E; Spira, Adam P
Abstract: Background: Anemia is associated with poorer sleep in children, and clinically, anemia is linked to insomnia. However, the association between anemia and insomnia in older adults is understudied. Methods: We examined the cross-sectional association between anemia and insomnia in 1, 053 adults (71.4 ± 10.6 years) in the Baltimore Longitudinal Study of Aging. Participants were classified as nonanemic, non-iron-deficient anemic, or iron-deficient anemic based on hemoglobin, ferritin, transferrin saturation, and mean cell volume. Insomnia symptoms were evaluated by the Women's Health Initiative Insomnia Rating Scale (WHIIRS). A total score (range 0–20) was generated, and participants were also classified as having 0, 1, or 2+ symptoms. Results: Overall, 10.5% of participants had non-iron-deficient anemia, 0.9% had iron-deficient anemia, and 88.5% had no anemia. Due to its low prevalence, the iron-deficient anemic group was dropped from analyses. In models adjusted for demographics, number of medical conditions, and Center for Epidemiologic Studies Depression Scale score, non-iron-deficient anemic individuals had significantly higher WHIIRS total scores, indicating greater insomnia severity, compared to those without anemia (predicted adjusted mean WHIIRS of 7.24 [95% confidence interval (CI): 6.40–8.08] vs 5.92 [95% CI: 5.65–6.19]). They also had twice the risk of reporting ≥2 insomnia symptoms (vs 0 symptoms; relative risk ratio = 2.20, 95% CI: 1.25–3.89). Conclusions: Results suggest that individuals with non-iron-deficient anemia are more likely to experience insomnia symptoms than those who are nonanemic. These results may have implications for insomnia treatment or the identification of underlying frailty in individuals with sleep problems.